Chronic periodontitis with familial aggregation and discordant identical twins - Sarah Christina Grech (University Library System, University of Pittsburgh, 2015)
Chronic periodontitis is an advancement of gingivitis that involves progressive attachment loss, pocketing, and bone loss around the teeth.  It has been linked to both genetic and environmental factors, making it a multifactorial disease.  This case examines a family of eight siblings with a 50% prevalence of chronic periodontitis. A strong genetic influence is not likely, since one identical twin in this family has chronic periodontitis, while the other twin is unaffected.  Environmental risk factors, including smoking, emotional stress, and poor oral hygiene, are present in all affected individuals, thus appearing to play a significant role in the development of periodontitis in this family.  It is important for a dentist to understand the etiology of the family's chronic periodontitis in order to provide proper treatment and management of risk factors so that good oral health can be maintained.